Empirical approach to estimate rock mass damage from long-hole winze (LHW) blasting - Fullelove, I.; Onederra, I.; Villaescusa, Ernesto (2017)
© 2016 Institute of Materials, Minerals and Mining and The AusIMM Published by Taylor & Francis on behalf of the Institute and The AusIMM.Long-hole winze (LHW) blasting is a critical stage of production in underground sublevel open stoping; however, its influence on potential excavation damage is often overlooked. In addition, recent developments in uphole LHW practices are implementing longer firing lengths, sometimes exceeding 15–20 m on a single blast. This has the potential to increase the likelihood of blast-related damage. This paper introduces an empirical approach to determine long-hole winze firing heights to minimise near-field rock mass damage. The degree of damage is estimated from the amplitude of peak particle velocities induced by the LHW blasts. Modelling was conducted to evaluate the relationship between peak particle velocity (PPV) as a function of LHW firing heights and distance to a point of interest. A hypothesis was established and further verified with direct measurements from a comprehensive near-field vibration monitoring programme conducted at a large sublevel open stoping operation in Australia. An empirical model to estimate PPV as a function of a non-dimensional factor was established. The model is defined by the ratio of the distance to a point of interest and the LHW firing height. This model may be used to determine the recommended advance and firing phases of a LHW to minimise potential damage to open stope boundaries.